2005
DOI: 10.2174/1381612053382142
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Agents: Studies on Fumagillin and Curcumin Analogs

Abstract: Cancer is a general term used to describe many disease states, each of which are characterized by abnormal cell proliferation. The causes which bring about this abnormal cellular behavior are specific to each type of cancer. The success of tumor-targeted therapy is limited by this diversity. One common denominator for all types of cancer is the requirement of a suitable blood supply. Therefore, tumor vasculature has emerged as a potential target for therapeutic intervention. New blood vessel growth from preexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Curcumin was shown to inhibit cancer (Conney et al, 1991;Huang et al, 1994), and was later reported to function as an angiogenic inhibitor (Arbiser et al, 1998). Since this report, the antiangiogenic effect of curcumin and its potential mechanism of action have been studied extensively in different models and organs (Adams et al, 2004;Furness et al, 2005;Bhandarkar and Arbiser, 2007;Kunnumakkara et al, 2008;Varinska et al, 2010). Several signaling transduction pathways have been found to be regulated by curcumin, including protein kinase C, NF-kappaB and AP-1 (Bhandarkar and Arbiser, 2007).…”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin was shown to inhibit cancer (Conney et al, 1991;Huang et al, 1994), and was later reported to function as an angiogenic inhibitor (Arbiser et al, 1998). Since this report, the antiangiogenic effect of curcumin and its potential mechanism of action have been studied extensively in different models and organs (Adams et al, 2004;Furness et al, 2005;Bhandarkar and Arbiser, 2007;Kunnumakkara et al, 2008;Varinska et al, 2010). Several signaling transduction pathways have been found to be regulated by curcumin, including protein kinase C, NF-kappaB and AP-1 (Bhandarkar and Arbiser, 2007).…”
Section: Curcuminmentioning
confidence: 99%
“…It has been shown that curcumin has direct antiangiogenic activity in vitro [205,206] and in vivo [206 -208], which may explain its chemopreventive effect at the level of tumour growth and metastasis. Possible antiangiogenic mechanisms are been postulated like the down regulation of proangiogenic genes such as VEGF and angiopoitin and a decrease in migration and invasion of endothelial cells [101].…”
Section: Effects Of Curcumin On Angiogenesismentioning
confidence: 99%
“…18, 19 and reviewed in refs. 3,20,21). In this context, curcumin induces apoptosis by a redox-dependent mechanism (18); reduction in the nuclear expression of nuclear factor-nB (19); inhibition of telomerase activity (22); down-regulation of Notch-1 signaling (23); and cytochrome c release, Bid cleavage and caspase-9 and caspase-3 activation, and down-regulation of the antiapoptotic proteins Bcl-2, Bcl-X L , and Myc (20,24).…”
mentioning
confidence: 99%